Digital Marketing Strategy Based on Sustainability Value in Improving Local Product Competitiveness - Anggraini, Sumiati; Hanifah, Muhammad (Jurnal Transformasi Digital dalam Ekonomi, Bisnis, dan Manajemen, 2025)
This study aims to examine the effect of digital marketing strategies based on sustainability values on improving the competitiveness of local products, using a mixed method approach that combines quantitative and qualitative analysis. The background of this research is based on the weak competitiveness of local products caused by the mismatch of marketing strategies with sustainability trends and increasing consumer preferences for ethical and environmentally friendly products. Quantitative data was collected through a survey of 150 digital consumers, while qualitative data was obtained through in-depth interviews with 10 UMKM players. The results show that the integration of sustainability values such as transparency, use of environmentally friendly materials, and social responsibility in digital strategies can increase positive consumer perceptions and strengthen purchase intentions. The qualitative findings support the quantitative results by revealing that businesses that implement these strategies are more adaptive in reaching digital consumers and strengthening local brand identity. The implications of this study show the importance of synergy between sustainability and digital transformation approaches to create sustainable competitiveness for local products. This research contributes to the development of sustainable digital marketing theory as well as strategic recommendations for UMKM and policy makers.